Logística y canales de distribución para la mejora de procesos. Estudio de Caso NEDERAGRO SA-Período 2019 - Mejía Moreira, Juan Alberto (2018)
The agricultural and agroindustrialsector of the country increase their demand due to economic incentives by the government, and the agrochemical companies increase their profitability due to their internal processes and continuous improvement. The objective of this research is to carry out a logistic evaluation of the distribution channels of Nederagro S.A. to increase incomes. The methodology used was a non-experimental cross-sectional design with non-probabilistic sampling for convenience. A questionnaire was applied to collect information, so as data collection techniques, the surveys of potential distributors and interviews of managers were used, in order to analyze the feasibility of expansion of the sales force towards Sierra region, and to optimize the delivery time of the products. The main results using the balanced scorecard, showed that because of the absence of a distribution center to accelerate the delivery process of the products due to the weak sales force, and quality assistance in sierra region, short and long-term strategies based on strategic objectives can be implemented, in order to increase the market share and get a greater number of customers, carrying out the standards of financial indicators and the actions presented to improve logistics processes and distribution chain.